2016
DOI: 10.1371/journal.pone.0162011
|View full text |Cite
|
Sign up to set email alerts
|

Protection of α-CaMKII from Dephosphorylation by GluN2B Subunit of NMDA Receptor Is Abolished by Mutation of Glu96 or His282 of α-CaMKII

Abstract: Interaction of CaMKII and the GluN2B subunit of NMDA receptor is essential for synaptic plasticity events such as LTP. Synaptic targeting of CaMKII and regulation of its biochemical functions result from this interaction. GluN2B binding to the T-site of CaMKII leads to changes in substrate binding and catalytic parameters and inhibition of its own dephosphorylation. We find that CaMKIINα, a natural inhibitor that binds to the T-site of CaMKII, also causes inhibition of dephosphorylation of CaMKII similar to Gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…It is also reported that the phosphorylation status of GluN2B at Ser 1303 also regulates GluN2B-CaMKII interaction ( Raveendran et al, 2009 ), whereas the phosphorylation status of Ser 1303 , in turn, is regulated by the action of kinases and phosphatases ( Ramya et al, 2012 ). In the GluN2B-bound state, the enzyme becomes resistant to the action of phosphatases ( Cheriyan et al, 2011 ) indicating GluN2B-induced structural changes which can be abolished by specific mutations in CaMKII ( Mayadevi et al, 2016 ). This could be a possible reason for the resistance of phospho-Thr 286 -CaMKIIα to phosphatases in the PSD ( Mullasseril et al, 2007 ).…”
Section: Ca 2+ /Calmodulin-dependent Protein Kinas...mentioning
confidence: 99%
See 2 more Smart Citations
“…It is also reported that the phosphorylation status of GluN2B at Ser 1303 also regulates GluN2B-CaMKII interaction ( Raveendran et al, 2009 ), whereas the phosphorylation status of Ser 1303 , in turn, is regulated by the action of kinases and phosphatases ( Ramya et al, 2012 ). In the GluN2B-bound state, the enzyme becomes resistant to the action of phosphatases ( Cheriyan et al, 2011 ) indicating GluN2B-induced structural changes which can be abolished by specific mutations in CaMKII ( Mayadevi et al, 2016 ). This could be a possible reason for the resistance of phospho-Thr 286 -CaMKIIα to phosphatases in the PSD ( Mullasseril et al, 2007 ).…”
Section: Ca 2+ /Calmodulin-dependent Protein Kinas...mentioning
confidence: 99%
“…Evidence obtained later was in accordance with these predictions on the final functional outcome of the switch, although it involved additional mechanisms than the predicted ones. Accordingly, the revised model ( Lisman and Raghavachari, 2015 ) predicts that energy efficiency is achieved by the reduced dephosphorylation rate of the GluN2B-bound CaMKII ( Cheriyan et al, 2011 ; Mayadevi et al, 2016 ). Stability against protein turnover is possible since protein turnover operates by subunit exchange between holoenzymes.…”
Section: Ca 2+ /Calmodulin-dependent Protein Kinas...mentioning
confidence: 99%
See 1 more Smart Citation